Carbon cycle and climate feedbacks under CO2 and non-CO2 overshoot pathways - I. Melnikova; I. Melnikova; P. Ciais; K. Tanaka; K. Tanaka; H. Shiogama; K. Tachiiri; K. Tachiiri; T. Yokohata; O. Boucher (Earth System Dynamics)
Reducing emissions of non-carbon dioxide (CO2) greenhouse gases (GHGs), such as methane (CH4) and nitrous oxide (N2O), complements CO2 mitigation in limiting global warming. However, estimating carbon–climate feedback for these gases remains fraught with uncertainties, especially under overshoot scenarios. This study investigates the impact of CO2 and non-CO2 gases with nearly equal levels of effective radiative forcing on the climate and carbon cycle, using the Earth system model (ESM) IPSL-CM6A-LR. We first present a method to recalibrate methane and nitrous oxide concentrations to align with published radiative forcings, ensuring accurate model performance. Next, we carry out a series of idealised ramp-up and ramp-down concentration-driven experiments and show that, while the impacts of increasing and decreasing CO2 and non-CO2 gases on the surface climate are nearly equivalent (when their radiative forcing magnitudes are set to be the same), regional differences emerge. We further explore the carbon cycle feedbacks and demonstrate that they differ under CO2 and non-CO2 forcing. CO2 forcing leads to both carbon–climate and carbon–concentration feedbacks, whereas non-CO2 gases give rise to the carbon–climate feedback only. We introduce a framework, building on previous studies that addressed CO2 forcing, to separate the carbon–climate feedback into a temperature term and a temperature–CO2 cross-term. Our findings reveal that these feedback terms are comparable in magnitude for the global ocean. This underscores the importance of considering both terms in carbon cycle feedback framework and climate change mitigation strategies.